Linguistic-cultural documentation and production of prototypes of educational material for the development of programs to strengthen and revitalize Quechua in human settlements in the Los Olivos-Lima district - López Capillo, Carmela Florencia (2021)
The article offers the results of a research study that documented speeches that represent the linguistic and cultural knowledge of Quechua speakers of the dialect groups: Ancash-Huaylas- Huánuco-Lima, Huancavelica-Ayacucho-Ica and Apurimac-Cuzco-Puno, with the purpose of developing materials for the revitalization of the original language in the human settlements Enrique Milla Ochoa, Laura Caller Iberico and Armando Villanueva del Campo of the Los Olivos district of Lima, urban areas in which the children of the founding migrants do not they speak. Through the use of the Internet and with the contribution of language cultivators, at first, graphic resources, audios and videos of interest were identified on different websites; later, it was collected, classified, adapted and translated literary, recreational and instructive texts to produce new materials under specific parameters; likewise, guides were developed to promote the natural transmission of the language, the activation of expressive skills in semi-linguists, nests of polidialectal languages, reading and writing workshops for fluent Quechua speakers and second language learning for Spanish-speaking monolinguals. The final products will also be used in new programs.